Prevalence, Characteristics, and Outcomes of Children With Congenital Heart Disease Undergoing Noncardiac Surgery in the Presence or Absence of COVID‐19 Infection During the Pandemic - David Faraoni; James A. DiNardo; Viviane G. Nasr (Journal of the American Heart Association: Cardiovascular and Cerebrovascular Disease)
Background Children with congenital heart disease undergoing noncardiac surgery are at increased risk of perioperative complications. The objectives of our study are (1) to describe the prevalence and characteristics of children undergoing noncardiac surgery in the presence or absence of COVID‐19 infection and (2) describe the association between preoperative diagnosis of COVID‐19 and outcomes. Methods We identified all children who underwent surgery between 2017 and 2022 in the American College of Surgeons National Surgical Quality Improvement Program pediatric database. Starting in 2021, the presence of a preoperative diagnosis of COVID‐19 was reported in the database. The outcomes included 30‐day mortality and the incidence of the following major postoperative outcomes: cardiac arrest, reintubation, pneumonia, sepsis, and readmission. A composite end point that includes the presence of at least 1 of the abovementioned complications was created. Results We identified 2919 patients with a preoperative diagnosis of COVID‐19 versus 537 622 without. Patients with a preoperative diagnosis of COVID‐19 underwent emergent procedures more often (64% versus 29%). Using multivariable logistic regression, the presence of preoperative diagnosis of COVID‐19 increased the incidence of the composite endpoint (odds ratio [OR], 1.37 [95% CI, 1.19–1.56]; P<0.001), as did the presence of CHD (OR, 2.06 [95% CI, 2.00–2.13]; P<0.001). Conclusions Our study describes the prevalence and characteristics of children with congenital heart disease undergoing noncardiac surgery during the COVID‐19 pandemic. We report that the preoperative diagnosis of COVID‐19 and the presence of congenital heart disease significantly increased the risk of complications.